Effect of Lanthanum Chloride on Reproductive Efficiency of Drosophila simulans - S, Renuka Jyothi; BP, Harini (Asian Journal of Biological and Life Sciences)
In present study, Drosophila simulans has been used as an experimental organism to know the efficacy of rare earth element (REE) metal, lanthanum chloride (LaCl3) on the reproductive efficiency as life history traits viz., copulation duration, fecundity and fertility are assessed with a focused aim of exposure to lethal concentrations The REE metal was mixed in cream agar media of wheat in graded doses of (LaCl3 0.02mg, 0.03mg, 0.04mg). D. simulans species were cultured in laboratory under standard conditions in a defined media. Third instar stage of larvae’s were used for the treatment by ingesting when they were actively crawling, boring and feeding voraciously. Results showed that on exposure of LaCl3 graded doses of concentration to treated versus the control showed reduced fecundity and fertility significantly (p<0.05), while the copulation duration increased in the treated flies than that of the control with different crosses. The studied element exhibited significant effect on the reproductive parameters and it may harmful if exposed more than a 10mg concentration naturally and effect on maximum flies diversity.
Keywords: Copulation duration; Drosophila simulans; Fecundity; Fertility; Lanthanum chloride